Influence of pH modifiers on the dissolution and stability of hydrochlorothiazide in the bi- and three-layer tablets - Blatnik Sandra Urek; Dreu Rok; Srčič Stanko (Acta Pharmaceutica)
During the past few years, the studies of bi- and multi-layered tablets increased due to the consumption of several different drugs per day by a patient and requests for appropriate patient compliance. The demographic shift toward older population increases the use of combination therapy as polypharmacy. Hydrochlorothiazide (HCTZ), as a model drug, is most commonly used in the treatment of hypertension, congestive heart failure and as a diuretic. The aim of the present study is to investigate the effect of the local environment on dissolution and stability behaviour of HCTZ in fixed multilayered tablet combinations, which are commonly used in polypharmacy. For this purposes, three different systems were introduced: (i) two conventional tablets (HCTZ and pH modifying placebo), (ii) 2-layer tablets (HCTZ, pH modifying placebo) and (iii) 3-layer tablets (HCTZ, barrier and pH modifying placebo). Disintegration of tablets, dissolution of HCTZ from tablets and HCTZ related substances were monitored for all systems. Results showed that there was a significant difference between dissolution profiles of the conventional two-tablet system (HCTZ tablet and pH modifying tablet) and the 2-layer and 3-layer tablets, which include the pH modifying layer. In the case of the conventional two-tablets system, 85 % of HCTZ was dissolved in less than 15 minutes. The dissolution profiles of HCTZ from 2-layered and 3-layered tablets showed a decrease in the dissolution rate. In addition, during the stability studies, it has been confirmed that the typical degradation product of HCTZ is formed, impurity B (4-amino-6-chloro-1,3-benzenedisulfonamide), which implies formation of formaldehyde as hydrolytic impurity not reported in the Ph. Eur. (16). Both impurities are particularly raised in 2-layered tablets with alkaline and neutral placebo layers. Stability of HCTZ was improved in the case of the 3-layer tablet, where the intermediate separation layer of glycerol monostearate was present. It is presumed that the HCTZ dissolution rate was decreased due to formation of non-soluble substances as a result of HCTZ degradation in the presence of alkaline layer.